EVALUSI SISTEM INFORMASI PELAYANAN PERIZINAN BERUSAHAAN SEKTOR INDUSTRI MELALUI ONLINE SINGLE SUBMISSION BERBASIS METODE TECHNOLOGY ACCEPTANCE MODEL DI DPM PTSP KABUPATEN GRESIK - Hendrik Ady Saputro; Nina Aini Mahbubah (SIGMA TEKNIKA, 2023)
The Online Single Submission (OSS) system has a very positive impact on business actors in making permit applications faster and simpler. The application of the OSS system requires an evaluation regarding the acceptance of the system. This is done so that it becomes a benchmark to assess the acceptance of an information technology by users. This research is motivated to analyze the acceptance of the Online Single Submission (OSS) information system using the Technology Acceptance Model (TAM). This method uses the TAM method, namely the user's perception of the ease of using technology (Perceived Ease of Use), the user's perception of the benefits / usefulness of technology (Perceived Usefulness), acceptance of information systems (Acceptance of IT) accepted by the community. This research was conducted by t-test and F-test. The results of the analysis show that the significant value in hypothesis-1 and hypothesis-2 indicates that the significance value is more than 0.05, which means that variable X has a significant effect on variable Y.